Early development of immune reconstitution inflammatory syndrome related to Pneumocystis pneumonia after antiretroviral therapy. (April 2014) - Mok, Hoi Ping; Hart, Elizabeth; Venkatesan, Pradhib
Immune reconstitution inflammatory syndrome is a recognized complication after the initiation of combination antiretroviral therapy (cART). We report a patient who developed life-threatening pulmonary immune reconstitution inflammatory syndrome (IRIS) three days after initiation of cART. We reviewed published cases of IRIS after Pneumocystis pneumonia (PCP), in particular the time from initiation of cART to IRIS event. The median duration from the initiation of cART to the onset of IRIS was 15 days in the 33 patients reviewed. This report alerts clinicians to the rapidity of the development of pulmonary IRIS following PCP after the initiation of cART.